Strategi dan Konsep Perancangan Pembangunan Semula Pusat Kota Lama di Malaysia - Mohd Razali Agus (JIP ( Jurnal Industri dan Perkotaan ), 2003)
This paper will discuss about the concept and strategies of the initial planning and development of the old city centres in the past. The city centres were open by Malay people.